Intramuscular Injection of miR-1 Reduces Insulin Resistance in Obese Mice - Rodrigues, Alice C.; Spagnol, Alexandre R.; Frias, Flávia de Toledo; de Mendonça, Mariana; Araújo, Hygor N.; Guimarães, Dimitrius; Silva, William J.; Bolin, Anaysa Paola; Murata, Gilson Masahiro; Silveira, Leonardo (Frontiers in Physiology, 2021)
The role of microRNAs in metabolic diseases has been recognized and their modulation may be a promising strategy to treat obesity and obesity-related diseases. The major purpose of this study was to test the hypothesis that intramuscular mir-1a-1 replacement therapy could improve metabolic parameters of mice fed a high-fat diet. To this end, we first injected miR-1a precursor intramuscularly in high-fat diet-fed mice and evaluated glucose tolerance, insulin sensitivity and adiposity. miR-1a-treated mice did not lose weight, but had improved insulin sensitivity measured by insulin tolerance test. Next, using an in vitro model of insulin resistance by treating C2C12 cells with palmitic acid (PA), we overexpressed miR-1a and measured phospho-Akt content and transcript levels of protein related to fatty acid oxidation. We found that despite miR-1a could not restore insulin sensitivity in C2C12 cells, as indicated by phospho-Akt levels, miR-1a increased expression of Pgc1a and Cpt1b in PA-treated cells, suggesting a possible role of miR-1a in mitochondrial respiration. Finally, we analyzed mitochondrial oxygen consumption in primary skeletal muscle cells treated with PA and transfected with or without miR-1a mimic. PA-treated cells showed reduced basal respiration, oxygen consumption rate-linked ATP production, maximal and spare capacity and miR-1a overexpression could prevent impairments in mitochondrial respiration. Our data suggest a role of miR-1a in systemic insulin sensitivity and a new function of miR-1a in regulating mitochondrial respiration in skeletal muscle.